TOPICAL ISSUES IN THE HISTORIOGRAPHY OF THE HISTORY OF JOURNALISM IN THE NORTH CAUCASIAN AUTONOMIES WITHIN THE PERIOD OF SOCIALIST MODERNIZATION IN THE REGION - Lema A. Turpalov (Izvestiâ Ûžnogo Federalʹnogo Universiteta: Filologičeskie Nauki, 2022)
The era of the formation of the Bolshevik authoritarian regime in the country (1917-1938) is the most studied segment of the history of journalism of the national regions of the North Caucasus. In the historiography of this stage of the development of the regional media system, three periods can be distinguished, each of which has its own characteristics. The first (1920-1950) is characterized by review articles published in specialized journalistic publications expressing the directives of the Bolshevik leadership in the field of press. At the second stage (1950-1990), a scientific study of the processes of the formation of an authoritarian model of regional journalism was originated, which was characterized by a one-sided approach from the position of Marxist ideology. With the collapse of the communist regime in 1991, a revision of the concepts of Soviet historical and journalistic science began. However, as for the studies devoted to the history of journalism in the North Caucasus, we can say that the problem is insufficiently studied.